Основы аккредитации лаборатории радиационного контроля: учебное пособие - Ефимов П. В. Павел Васильевич; Сертаков Ю. И. Юрий Иванович; Алхимов Ю. В. Юрий Васильевич; Кулешов В. К. Валерий Константинович (Томск, Изд-во ТПУ, 2010)
Заглавие с титульного экрана